2023
DOI: 10.1001/jamaneurol.2023.2226
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality With Alzheimer Disease and Related Dementias as an Underlying or Contributing Cause During the COVID-19 Pandemic in the US

Abstract: ImportanceAdults with Alzheimer disease and related dementias (ADRD) are particularly vulnerable to the direct and indirect effects of the COVID-19 pandemic. Deaths associated with ADRD increased substantially in pandemic year 1. It is unclear whether mortality associated with ADRD declined when better prevention strategies, testing, and vaccines became widely available in year 2.ObjectiveTo compare pandemic-era excess deaths associated with ADRD between year 1 and year 2 overall and by age, sex, race and ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Regarding the place of death in the pre-pandemic period, 67.44% of deaths (dementia and AD) occurred at home, increasing to 77.84% of deaths at home during the pandemic period. Our findings align with similar trends reported by Chen et al., 14 who observed a significant increase in deaths that occurred at home among older people with AD and dementia, compared to those that occurred in nursing homes. This change can be attributed to the unique circumstances of the COVID-19 pandemic, where due to fear of transmission, many home care clients canceled in-person visits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the place of death in the pre-pandemic period, 67.44% of deaths (dementia and AD) occurred at home, increasing to 77.84% of deaths at home during the pandemic period. Our findings align with similar trends reported by Chen et al., 14 who observed a significant increase in deaths that occurred at home among older people with AD and dementia, compared to those that occurred in nursing homes. This change can be attributed to the unique circumstances of the COVID-19 pandemic, where due to fear of transmission, many home care clients canceled in-person visits.…”
Section: Discussionsupporting
confidence: 93%
“…Their results indicated a large increase in mortality in the first year of the pandemic, with excess deaths in long-stay health homes; and a decrease in mortality in the second year of the pandemic, with excess deaths at home and medical centres. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The adoption of telemedicine emerged as a preferred approach by which to minimize hospital visits, and potentially fewer patients required hospitalization as a result. Additionally, initial data indicate that vaccinations play a pivotal role in reducing the severity of disease manifestations, further limiting the necessity for hospital admissions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data for more recent years are still being compiled, but one study found that deaths due to all dementias, including Alzheimer's, decreased between March 2021 and February 2022, in particular among residents of nursing homes and long‐term care facilities. 417 …”
Section: Mortality and Morbiditymentioning
confidence: 99%